Asymmetric Synthesis of Axinellamines A and B - Ma, Zhiqiang (Angew Chem Int Ed Engl, 2016)
Axinellamines A and B are broad-spectrum anti-bacterial pyrrole–imidazole alkaloids that have a complex polycyclic skeleton. A new asymmetric synthesis of these marine sponge metabolites is described herein, featuring an oxidative rearrangement and an anchimeric chlorination reaction.